Return to Sport Following High Tibial Osteotomy With Concomitant Osteochondral Allograft Transplantation. Issue 8 (July 2020) - Liu, Joseph N.; Agarwalla, Avinesh; Christian, David R.; Garcia, Grant H.; Redondo, Michael L.; Yanke, Adam B.; Cole, Brian J.
Background: Young patients with symptomatic chondral defects in the medial compartment with varus malalignment may undergo opening wedge high tibial osteotomy (HTO) with concomitant osteochondral allograft transplantation (OCA) (HTO + OCA). Although patients have demonstrated favorable outcomes after HTO + OCA, limited information is available regarding return to sporting activities after this procedure. Purpose: To evaluate (1) the timeline to return to sports (RTS), (2) patient satisfaction, and (3) reasons for discontinuing sporting activity after HTO + OCA, and to identify predictive factors of RTS. Study Design: Case series; level of evidence, 4. Methods: Consecutive patients who underwent HTO + OCA for varus deformity and medial femoral condyle focal chondral defects with a minimum 2-year follow-up were retrospectively reviewed. Patients completed a subjective sports questionnaire, satisfaction questionnaire, visual analog scale for pain, and Single Assessment Numerical Evaluation. Results: Twenty-eight patients with a mean age of 36.97 ± 7.52 years were included at mean follow-up of 6.63 ± 4.06 years. Fourteen patients (50.0%) required reoperation during the follow-up period, with 3 (10.7%) undergoing knee arthroplasty. Twenty-four patients participated in sports within 3 years before surgery, with 19 patients (79.2%) able to return to at least 1 sport at a mean 11.41 ± 6.42 months postoperatively. However, only 41.7% (n = 10) were able to return to their preoperative level. The most common reasons for sports discontinuation (n = 20; 83.3%) were a desire to prevent further damage to the knee (70.0%), persistent pain (55.0%), persistent swelling (30.0%), and fear (25.0%). Conclusion: In young, active patients with varus deformity and focal medial femoral condyle chondral defects, HTO + OCA enabled 79.2% of patients to RTS by 11.41 ± 6.42 months postoperatively. However, only 41.7% of patients were able to return to their preinjury level or better. It is imperative that patients be appropriately educated to manage postoperative expectations regarding sports participation after HTO + OCA.